Infiltration by CXCL10 Secreting Macrophages Is Associated With Antitumor Immunity and Response to Therapy in Ovarian Cancer Subtypes - Ardighieri, Laura; Missale, Francesco; Bugatti, Mattia; Gatta, Luisa Benerini; Pezzali, Irene; Monti, Matilde; Gottardi, Stefano; Zanotti, Laura; Bignotti, Eliana; Ravaggi, Antonella; Tognon, Germana; Odicino, Franco; et al. (Frontiers in Immunology, 2021)
Ovarian carcinomas (OCs) are poorly immunogenic and immune checkpoint inhibitors (ICIs) have offered a modest benefit. In this study, high CD3+ T-cells and CD163+ tumor-associated macrophages (TAMs) densities identify a subgroup of immune infiltrated high-grade serous carcinomas (HGSCs) with better outcomes and superior response to platinum-based therapies. On the contrary, in most clear cell carcinomas (CCC) showing poor prognosis and refractory to platinum, a high TAM density is associated with low T cell frequency. Immune infiltrated HGSC are characterized by the 30-genes signature (OC-IS30) covering immune activation and IFNg polarization and predicting good prognosis (n=312, TCGA). Immune infiltrated HGSC contain CXCL10 producing M1-type TAM (IRF1+pSTAT1Y701+) in close proximity to T-cells. A fraction of these M1-type TAM also co-expresses TREM2. M1-polarized TAMs were barely detectable in T-cell poor CCC, but identifiable across various immunogenic human cancers. Single cell RNA sequencing data confirm the existence of a tumor-infiltrating CXCL10+IRF1+STAT1+ M1-type TAM overexpressing antigen processing and presentation gene programs. Overall, this study highlights the clinical relevance of the CXCL10+IRF1+STAT1+ macrophage subset as biomarker for intratumoral T-cell activation and therefore offers a new tool to select patients more likely to respond to T-cell or macrophage-targeted immunotherapies.